A Neuro-Fuzzy Controller for Compensation of Voltage Disturbance in SMIB System - Budi Srinivasarao; G. Sreenivasan; Swathi Sharma (Institute of Advanced Engineering and Science, 2017)
Since last decade, due to advancement in technology and increasing in the electrical loads and also due to complexity of the devices the quality of power distribution is decreases. A Power quality issue is nothing but distortions in current, voltage and frequency that affect the end user equipment or disoperation; these are main problems of power quality so compensation for these problems by DPFC is presented in this paper. The control circuits for DPFC are designed by using line currents, series reference voltages and these are controlled by conventional Neuro-Fuzzy controllers. The results are observed by MATLAB/SIMULINK model.